2014
DOI: 10.1371/journal.pone.0095983
|View full text |Cite
|
Sign up to set email alerts
|

Anti-VEGF-A Affects the Angiogenic Properties of Tumor-Derived Microparticles

Abstract: Tumor derived microparticles (TMPs) have recently been shown to contribute to tumor re-growth partially by inducing the mobilization and tumor homing of specific bone marrow derived pro-angiogenic cells (BMDCs). Since antiangiogenic drugs block proangiogenic BMDC mobilization and tumor homing, we asked whether TMPs from cells exposed to an antiangiogenic drug may affect BMDC activity and trafficking. Here we show that the level of VEGF-A is reduced in TMPs from EMT/6 breast carcinoma cells exposed to the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…We speculate that these phenomena may be due to differences between cytotoxic drugs, which induce tumor cell apoptosis and anti-angiogenic agents, which inhibit endothelial cells instead of tumor cells and do not cause apoptosis. This is consistent with previous reports (21,22). The number of tumorderived microparticles (TMPs) was significantly increased in breast carcinoma cells exposed to paclitaxel chemotherapy compared to the number in untreated tumor cells (21), but treatment with anti-VEGF-A neutralizing antibodies, which is a cytostatic drug, did not lead to a significant change in the number of TMPs (22).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We speculate that these phenomena may be due to differences between cytotoxic drugs, which induce tumor cell apoptosis and anti-angiogenic agents, which inhibit endothelial cells instead of tumor cells and do not cause apoptosis. This is consistent with previous reports (21,22). The number of tumorderived microparticles (TMPs) was significantly increased in breast carcinoma cells exposed to paclitaxel chemotherapy compared to the number in untreated tumor cells (21), but treatment with anti-VEGF-A neutralizing antibodies, which is a cytostatic drug, did not lead to a significant change in the number of TMPs (22).…”
Section: Discussionsupporting
confidence: 92%
“…A previous study demonstrated that MM MVs exposed to bortezomib had lower expression levels of angiogenic factors, which limited the proliferation and migration of these endothelial cells (23). Similarly, another study showed that the expression level of VEGF-A was decreased in TMPs from breast carcinoma cells exposed to anti-VEGF-A antibody and thereby reduced the angiogenic potential (22). However, the impact of anti-angiogenic therapy with lenalidomide has not been elucidated; moreover, the effects of bortezomib-or lenalidomide-exposed MVs on the NF-κB activity of endothelial cells have not been reported.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a different study, the anti-VEGF-A antibody B20 reduced the level of VEGF-A enclosed in breast cancer cell-secreted microparticles and these vesicles were unable to activate endothelial cells and could not promote BM-derived pro-angiogenic cell colonization [87]. In addition, exosomes derived from hematological tumor cells such as chronic myelogenous leukemia cells and MM cells also contribute to angiogenesis [8891].…”
Section: Effect Of Tumor-derived Evs On Bm-derived Cellsmentioning
confidence: 99%
“…Although traditionally thought of as signaling mediated primarily through soluble factors, the role of microvesicles and in particular TMVs in paracrine signaling through the horizontal transfer of bioactive molecules, is becoming more and more appreciated. The transfer of pro‐angiogenic cargos, for example, including EGFRvIII, VEGF, TGF‐β, and miRNA 1246 can significantly impact tumorigenesis . TMV‐mediated signaling can also serve to form a robust pro‐tumorigenic niche by signaling to and activating fibroblasts in the tumor microenvironment.…”
Section: Current Perspectives On Tmv Formation Cargo Enrichment Andmentioning
confidence: 99%